Quality and competitiveness of educational services in the view of students: problems and perspectives - Olga F. Piralova; Natalya A. Uimanova; Marina V. Olinder; Aleksandr А. Shumeiko; Elena V. Kulesh; Zhanna V. Korobanova; Tatiana B. Lisitsyna (Revista on line de Política e Gestão Educacional)
Nowadays, various transformations are taking place in higher education in Russia, which is primarily determined by the fact that the issue of ensuring the quality of educational services, increasing the requirements for the level of university graduates - future specialists and the introduction of new teaching methods is quite acute. The research aims to study the peculiarities of students' perception of the quality of education. As a research method, we used a questionnaire survey to quickly and effectively investigate students' idea of the quality of educational services provided to them. The article examines students' attitude to the education they receive and reveals the students' representation of the demand for the education they receive in the labor market. The study's novelty and originality lie in the fact that students' ideas about the quality of educational services are considered. It is revealed that the knowledge that graduates receive is evaluated as high quality, and several shortcomings identified by students in professional training (insufficient knowledge of practical skills, foreign languages) are revealed. It is shown that according to graduates, the level of training of specialists mainly meets the requirements of the labor market. The practical significance of the data obtained in this work lies in their use in social psychology, age psychology, marketing, and further theoretical development of this issue.